Eating Bananas Outside the National Museum: Unlimited Semiosis. Issue 4 (December 2021) - Krakowska, Joanna
Abstract : The banana protest, a mass reenactment of Consumer Art (1972), a series of photographs by Natalia LL that was removed from the National Museum in April 2019, was staged as a grassroots protest against this act of censorship and the Polish conservative government's "decency" policy as well as the underrepresentation of women's art in museums and galleries.